Temat twórczości we wczesnej poezji Anny Achmatowej. Finał książki „Różaniec” (1914) - Owsiannikowa, Swietłana (Studia Rossica Posnaniensia, 2011)
The article is dedicated to the analysis of the final of Beads by great Russian poetess Anna Akhmanova. The book’s final consists of just nine verses, but, nevertheless, it is beautiful and amazing. In a relatively brief article the author tries to acquaint us with a very complex, multicolored world created by the poetess and also attempts to bring to a focus the deep, sharp feelings of lyric heroine.